Estimation of ventricles size of human brain by Magnetic Resonance Imaging in Nepalese Population: A retrospective study - Singh, Sushma; Sharma, Bhoj Raj; Prajapati, Urusha; Sharma, Pujan; Bhatta, Manoj; Paudel, Nawaraj (Journal of Gandaki Medical College-Nepal, 2020)
Background and Objective: Magnetic resonance imaging (MRI) provides image acquisition of three-dimensional data and measurement in any chosen imaging plane. Objective of this study is to assess the size of ventricles of the brain of normal Nepalese people and establish the range of size of the ventricular system and compute the ventricular dimensions among different age and gender.Materials and methods: This is a cross-sectional retrospective study done at Gandaki Medical College, Pokhara. A total of 106 MRI scan data of healthy individuals were collected over a period of seven months between March to September 2019. Patients ranged between eight and eighty years of age with 58 males and 48 females. Measurements of the mean of bifrontal diameter (BFD), bihemispheric diameter (BHD), third ventricle transverse dimension (TVTD), fourth ventricle antero-posterior dimension (FVAP), fourth ventricle width (FVW), and frontal horn ratio (FHR) were done.Result: The mean of BFD, BHD, TVTD, FVAP, FVW, and FHR were found to be 3.05 ± 0.10 cm, 10.11 ± 0.40 cm, 0.43 ± 0.11 cm, 0.90 ± 0.11 cm, 1.22 ± 0.12 cm, and 0.30 ± 0.01 cm, respectively. The mean width of fourth ventricle in males and females was observed to be 1.23 ± 0.12 cm and 1.19 ± 0.11 cm respectively. There was a significant correlation of TVTD, FVAP, FHR and BFD with age with Pearson correlation coefficient 0.393 (P value